Inhibition of bacterial growth around gutta percha cones by different antimicrobial solutions using antibiotic sensitivity test (An in vitro study) - Nagham A Al-Hyali (College of Dentistry/ University of Baghdad, 2013)
Background: Decontamination of gutta percha cones was important factor for success of root canal treatment. The aim of the present in vitro study was to identify and to compare the antimicrobial effect of following disinfection solutions: 0.2% chlorhexidine gluconate, Iodine, tetracycline hydrochloride solution, EDTA & formocresol mixed with zinc oxide eugenol, on E faecalis, E coli and Candida albicans using sensitivity test Materials and Methods: Three types of microorganisms were isolated from infected root canals (E faecalis, E coli and Candida albicans) and cultured on Mueller Hinton agar petri-dishes. Disinfection of gutta percha cones done by immersion in six disinfection solutions (six groups), the groups are: distill water (used as control group), 0.2% chlorhexidine gluconate, Iodine, tetracycline hydrochloride solution, EDTA & formocresol mixed with Zinc oxide eugenol. The immersion times were 5 min. and the incubation was aerobically at 37 C for 24 hr. for bacterial species and at 28C for 48 hr. for candida albicans. After incubation, zones of inhibition (no growth of bacteria) were examined around the gutta percha cones & diameters of the zones were measured with a boley gauge. The means of inhibition zones for each group were measures and statistically analyzed among groups using ANOVA and LSD tests at 0.05 significance level. Results: There is highly significant differences (P=0.000) among all the tested groups. 0.2% Chlorhexidine gluconate showed the maximum antibacterial efficacy (broader zones of inhibition) against E faecalis. Compound of formocresol + Zinc oxide eugenol showed the maximum antibacterial efficacy against Candida albicans, and E coli. The minimum antibacterial efficacy against Candida albicans occurred with tetracycline group, while against E faecalis and E coli occurred with EDTA group Conclusion: All the tested materials had antibacterial efficacy against Candida albicans, E faecalis and E coli; but chlorhexidine gluconate and compound of formocresol & Zinc oxide eugenol, are more effective agents for a rapid disinfection of gutta-percha cones in five minutes.